Antibacterial synergism of selected compounds against MDR UTI pathogenic bacteria. - ARCHANA MOON; PRANJALI GAJBHIYE; MONALI JARIYA; DEEBA KHAN; AMIT TAKSANDE (International Journal of Pharma and Bio Sciences, 2017)
UTI is an infection of the urinary tract, caused by microbes including fungi, viruses, and bacteria. Bacteria are the most common cause of UTIs. The bacterium Escherichia coli (E. coli) causes the vast majority of UTIs. Urinary tract infections are the second most common type of infection in the body; accounting for about 8.1 million visits to health care providers each year. Women are especially prone to UTIs for anatomical reasons. For women, the lifetime risk of having a UTI is greater than 50 percent. Antibiotic resistant is a seriously growing problem in medicine. Limited treatment options are available for treatment of infections caused by MDR bacterial strains. Hence, there is an urgent need to search for novel, cost effective, potent therapeutic antibacterial agents. In the current study, we focused on investigation of antibacterial activity of selected phytochemicals against multidrug resistant bacterial isolates. The synergistic effect of antibacterials was checked to ensure drugs working together -where one drug increases the other’s effectiveness.